P058 Developing a Youth Health Care guideline on sexual development with limited evidence - Maris, S; Deurloo, J; Lanting, C; Kamphuis, M; Vlugt, I van der (BMJ quality & safety, 2013)
Background Children’s sexual development starts at an early age and is a very complex subject, comprising the physical but also the psychosocial development. Youth Health Care (YHC) professionals can prevent and detect problems in sexual development, and play a guiding role in stimulating sexual competency and positive sexual attitudes. Objectives Our goal was to develop an evidence based national YHC guideline for sexual development. Methods The content of the guideline is based on (inter)national guidelines, literature searches, consensus and experience. The guideline is now piloted for use in daily practice by YHC professionals. The way we handled the limited amount of evidence and the results of this pilot will be presented. We cooperated with an international centre of expertise on sexual and reproductive health and performed literature searches for a selected number of questions. Results The guideline describes the (physical and psychosocial) sexual development of children from 0–19 years old, determinants of sexual health and groups at risk. Discussion In this presentation, we would like to discuss the issue of dealing with the limited amount of evidence and we will show how we handled this issue. Working together with an experienced centre was crucial. Coming to consensus in the working group and performing a pilot test in addition, is essential in gaining obtaining support for the recommendations of the guideline. Implications for Guideline Developers/Users In YHC not much evidence of high quality is available. Exchange of experiences will help other guideline developers dealing with this as well.